TEOREMA TITIK TETAP FUNGSI YANG KONTRAKSI TEGAS - Michael Inuhan; Ch. Rini Indrati (Diponegoro University, 2019)
In this paper, it will be discussed some fixed point theorems in ultrametric spaces. By using spherically complete properties, it can be shown that there exists a unique fixed point of strictly contractive function. At the end, it will be shown there exists fixed point of strictly contracting on orbits function.